RESTORATIVE JUSTICE BAGI TERPIDANA PEMAKAI NARKOTIKA GOLONGAN 1 - Rospita Adelina Siregar; Lila Pitri Widi Hastuti (Jurnal MHKI, 2021)
Restorative Justice for convicted users of Narcotics class 1 is a normative juridical study that examines the results of decision No.111 / Pid. Sus / 2017 / PN Sag, with an emphasis on the problem of prison sentences determined based on evidence, the defendant violated Article 111 paragraph 2 of Law number 35 In 2009 concerning Class 1 Narcotics, the judge sentenced the defendant to a sentence of 8 months in prison and a fine of Rp. 1 billion. The defendant's confession that marijuana leaves were used as a treatment for his wife, who had been paralyzed for three years, was often in shock due to suffering from syringomyelia. Sentencing imprisonment for class 1 Narcotics users is seen as not causing a deterrent effect and even creates new problems, namely overcapacity in prisons/detention centres. For example, in the DKI Jakarta Regional Office, the capacity of prisons/detention centres is 319%. It is time to apply Restorative Justice and leave retributive Justice as a reform of criminal law to solve cases of misuse of Narcotics class 1.